2016
DOI: 10.1002/chem.201601320
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Electrophile Coupling of Vinyl Halides with Alkyl Halides

Abstract: An improved method for the reductive coupling of aryl and vinyl bromides with alkyl halides is presented that achieves high yields for a variety of substrates at rt with a low (2.5 to 0.5 mol%) catalyst loading. Under the optimized conditions, difficult substrates, such as unhindered alkenyl bromides, can be coupled to furnish the desired olefins with minimal diene formation and good stereoretention. These improved conditions also work well for aryl bromides. For example, a gram-scale reaction is demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…[1,2] For instance,a lthough the Wurtz and Ullmann reactions have been disclosed for more than ac entury, [3] only recently was an ickel-catalyzed reductive protocol explored for C(sp 3 )À C(sp 3 )a nd C(sp 3 )ÀC(sp 2 )b ond constructions based on the coupling of alkyl halides with other electrophiles. [4][5][6][7][8][9] In this context, good to excellent chemoselectivities have been achieved. Weix and co-workers further demonstrated that ap alladium and nickel dual catalytic method enabled efficient construction of aryl-aryl and vinyl-vinyl CÀC bonds through the equimolar reactions of C(sp 2 )-bromides with C(sp 2 )-triflates.…”
mentioning
confidence: 99%
“…[1,2] For instance,a lthough the Wurtz and Ullmann reactions have been disclosed for more than ac entury, [3] only recently was an ickel-catalyzed reductive protocol explored for C(sp 3 )À C(sp 3 )a nd C(sp 3 )ÀC(sp 2 )b ond constructions based on the coupling of alkyl halides with other electrophiles. [4][5][6][7][8][9] In this context, good to excellent chemoselectivities have been achieved. Weix and co-workers further demonstrated that ap alladium and nickel dual catalytic method enabled efficient construction of aryl-aryl and vinyl-vinyl CÀC bonds through the equimolar reactions of C(sp 2 )-bromides with C(sp 2 )-triflates.…”
mentioning
confidence: 99%
“…mol%], Mn 0 reductant, and DMPU as a solvent (Scheme 5, Condition B). 19 Under these conditions, unhindered alkenyl bromides, coupled well to give the desired alkenes with minimal diene formation and good stereoretention.…”
Section: Short Review Syn Thesismentioning
confidence: 97%
“…17,18 Running the reaction under the optimal conditions, but omitting TMSBr confirms that this additive is critical for obtaining high yields of 3a (entry 8). 19,20 We note that these optimal reaction conditions employ a 1:1 stoichiometry of the two electrophiles and only 10 mol % catalyst loading.…”
mentioning
confidence: 99%